SYNERGISTIC INTERACTION OF ADENOSINE DIPHOSPHATE - EPINEPHRINE AND EPINEPHRINE - COLLAGEN IN AGGREGATION OF HUMAN PLATELETS - Razi, Muhammad Shamaun; Butt, Idrees Farooq; Ayub, Muhammad; Aslam, Muhammad; Hameed, Waqas; Badar, Ahmed; Afzal, Muhammad Nasir (Journal of Ayub Medical College Abbottabad, 2004)
Background: Efficient hemostasis in human body depends on a complicated series of events which actively involve blood platelets. Platelets exhibit diverse responses in a variety of agonists. In vivo, most of the agonists act in synergism, causing aggregation of platelets. Methods: In this study, the synergism between ADP - Epinephrine and Epinephrine - Collagen has been determined by means of turbidometric method, which measures changes in optical density of platelet suspension. The study was carried out at the department of Hematology, Armed Forces Institute of Pathology, Rawalpindi. The subthreshold concentrations of each of the agonists were established with the help of dose response curve. By adding these agonists in subthreshold concentrations, the synergism between ADP - Epinephrine and Epinephrine - Collagen was determined. Results: The combinations of these agonists in subthreshold levels showed the synergistic responses in causing platelet aggregation. Conclusion: These findings indicate that the optimal platelet aggregation does occur between the above mentioned pairs of agonists even when each of the agonist is added to the other in subthreshold doses. Keywords: Platelet aggregation, agonist, synergism, Adenosine diphosphate, Collagen, Epinephrine